(untitled) - Dahl, Dale C (New York, 1977)
This book provides an understanding of the economic organization and operation of the food and fiber sector of the U. S. economy. It provides good treatment of agricultural price analysis. There are also a number of texts that consider the various dimensions of the marketing systemn for agricultural inputs, farm products, and processing and distribution activities.
Phân tích giá trong thị trường nông nghiệp
Keywords: Agricultural industries,Agricultural prices; United States,United States